2021
DOI: 10.2495/cmem210101
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Gear Design: Translation of the Results of Single Tooth Bending Fatigue Tests Through the Combination of Numerical Simulations and Fatigue Criteria

Abstract: Establishing the actual gear root bending strength is a fundamental aspect in gear design. With this respect, gears materials can be characterized through two types of tests, i.e. on Running Gears (RG) or Single Tooth Bending Fatigue (STBF). The former is able to reproduce the loading conditions of the actual gears and, therefore, leads to the most accurate results. The latter excels in terms of efficiency and simplicity of the experimental campaign but as a drawback, tends usually to overestimate the material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In recent studies, the authors pointed out that the FE simulation results of the STBF configuration can be analyzed and elaborated via different fatigue criteria based on the critical plane approach [41][42][43]. These allow for evaluating the criticality of each point along the ρ f P .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, the authors pointed out that the FE simulation results of the STBF configuration can be analyzed and elaborated via different fatigue criteria based on the critical plane approach [41][42][43]. These allow for evaluating the criticality of each point along the ρ f P .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it permits to individuate the potential propagation direction of the crack after nucleation. Nevertheless, it has been observed that different fatigue criteria could lead to different results in terms of TBS and/or crack propagation direction [42].…”
Section: Introductionmentioning
confidence: 99%
“…Material Design & Processing Communications case and the actual case [23, 36-39, 52, 53]. On the one hand, the lack of the rolling/sliding condition implies that the loading condition occurring within the toot root is different [11,54,55]. On the other hand, the fact that the tests are performed on the teeth rather that gear implies a statistical difference [17,18].…”
Section: Gear Testing For Tooth Root Bending Fatiguementioning
confidence: 99%
“…By considering the modal parameters of the structures and the influence of structural dynamic characteristics on micro-structural deformation, the factors that influence vibration fatigue damages were studied. Concli, F. [ 17 ] studied the different fatigue criteria according to different results of crack propagation direction. Poursaeidi and Arhani [ 18 ] investigated the failure of an auxiliary steam turbine.…”
Section: Introductionmentioning
confidence: 99%